DEMAND ANALYSIS OF TAXI AND PUBLIC RENTAL TRANSPORTATION AT I GUSTI NGURAH RAI INTERNATIONAL AIRPORT BALI - Ni Putu Delima Yogeswari Saraswati; Putu Alit Suthanaya; Aliya Ashra Indrasani (Jurnal Ilmiah Teknik Sipil, 2025)
: I Gusti Ngurah Rai International Airport is one of Indonesia’s primary air transportation gateways, which has experienced a significant increase in passenger mobility following the Covid-19 pandemic. With the rising number of arriving passengers, the demand for ground transportation to and from the airport has become a crucial aspect of travel connectivity. This study aims to analyze the characteristics of transportation mode users, the probability of selecting taxis and rental transportations, as well as the optimal fleet requirements at I Gusti Ngurah Rai International Airport. The research employs a stated preference technique with a binary logit difference model analysis. Primary data were obtained through surveys of domestic passengers and ground transportation drivers in the domestic arrival area, while secondary data were collected from various relevant agencies. The results indicate that the probability of users choosing a taxi is 2.32% and that of choosing a rental transportation is 3.86%. Consequently, the projected requirements are 27 taxi units and 44 rental transportation units in 2025, 30 taxi units and 51 rental transportation units in 2030, and 35 taxi units and 58 rental transportation units in 2035, based on the demand level of domestic flight passengers. The number of taxis and rental transportations currently available at I Gusti Ngurah Rai International Airport exceeds the projected fleet requirements.